A study on the implementation of capital budgeting techniques by Bumiputra Companies (Class B) in Selangor / Ismail Abdul Jalil - Abdul Jalil, Ismail (1997)
This research paper present the outcomes of (Class B) Bumiputra construction companies which employ capital budgeting techniques in their decision making process. Seven companies were selected from the population, two companies employ capital budgeting techniques and the other five do not. Project selected were projects from the year 1994, and 1995. The area of the study is in Selangor and Class B Bumiputra companies. The costs of projects range from RM2 million to RM8 million.